A COMPARATIVE STUDY ON THE EFFECT OF SISAL FIBRE AND WASTE PLASTIC STRIPS IN STRUCTURAL STRENGTH IMPROVEMENT OF TROPICAL BLACK CLAY - YOHANNA PAUL; BADAMASI ABDULRAHMAN; ISHOLA KAZEEM; ODOH KELVIN CHUKWUEBUKA; ABDULKADIR MOHAMMED NYAKO; FWANGSHAK GAYUS MIJE (Journal of Engineering Studies and Research)
A study on the effect of sisal fibre and waste plastic strips on tropical black clay (also called Black cotton soil, BCS) was carried out. Tests piloted on the natural and treated soil consist of California bearing ratio (CBR), Atterberg limits and compaction for different percentages inclusion of sisal fibre (0, 0.5, 1, 1.5 and 2%) and waste plastic strips (0, 0.5, 1, 1.5 and 2%) by dry weight of soil. Results obtained showed that the liquid limit of BCS initially fluctuated between 43.4% and 55.9% at 1% sisal fibre content, then dropped to 49.4% at 2% sisal fibre content. In the case soil treated with waste plastic strips, liquid values increased from 43.4% for the natural soil to a highest value of 58% at 1% waste plastic strips and thereafter decreased to 49.15% at 2% waste plastic strips content. Plastic limit for both BCS-sisal fibre/ waste plastic strips initially decreased from its natural value of 25.78 to 15.55 and 14.77% when treated with sisal fibre and waste plastic strips respectively at 0.5% admixtures content. In the case of plasticity index, values initially increase from its natural value of 17.66% to peak values of 35.39 and 43.23% for sisal fibre and waste plastic strips treated soil respectively, and thereafter decreased. Maximum dry density (MDD) initially increased from 1.55 mg/m3 at 0%, to 1.60 mg/m3 at 0.5% and thereafter decreased to 1.53 mg/m3 at 2% of fibre content. In the case of samples treated with waste plastic strips. The MDD progressively increased as the amount of waste plastic strips increased. OMC show an overall trend of increase for BCS treated with sisal fibre, and a general trend of decrease for soil treated with waste plastic strips. The CBR values initially lessened from their natural value of 13.59% to 4.76% at 1% sisal fibre and subsequently increased to 10.57% at 2% sisal fibre. Similar behaviour was observed for soil modified with waste plastic strips. Based on the results, BCS/waste plastic strips improved the soil more than BCS/sisal fibre treated soil and is recommended at optimal 2% waste plastic strips for geotechnical engineering application such as road payment.